Morphological and genetic variation of Eusideroxylon zwageri Teijsm. & Binn. (Borneo ironwood) in Sarawak, Malaysia - Md Isa, Siti Fatimah (2020)
Previously, two species were recognized as Borneo Ironwood, Eusideroxylon zwageri and E. melagangai. However, study revealed that E. melagangai is belonging to a new genus called Potoxylon. This confusion is due to the close morphological resemblance between both species. Borneo Ironwood has high demand and high market value because of its valuable and durable timber, which has put its number at risk of illegal logging. In addition to threats from illegal logging, the slow seed germination process delays their natural regeneration in the forest. It may take up to six months in their natural environment to germinate. Other than that, poor genetic matching of planting material to the planting site or using seed from small, inbred populations can result, for instance, in reducing growth, reproductive output, the ability to resist pests and capacity to adapt to environmental variation. In this project, two sampling areas were chosen (i) Nirwana Rehabilitation Forest (NRF), UPM Bintulu Campus, and (ii) fragmented area in Tatau, Bintulu, Sarawak. The aims for this study were to document morphological features of E. zwageri and to recognize their varieties by using conventional method based on the macro-morphology characters and to support the outcome with cladistics analysis. Subsequently, four microsatellite markers were used to analyse E. zwageri genetic variation and their clustering to the varieties based on allelic data. In addition, the identification of fungi isolated from the fruits of E. zwageri was also conducted. Three varieties of E. zwageri were identified namely; zwageri, grandis, and exilis. These varieties were recognized based on the seed, bark and leaves traits and supported with cladistics analysis and allelic data. Meanwhile, genetic study shown that 20.1% of total genetic variation corresponded to differences between populations while 79.9% was attributed by differences between individuals. The Tatau (Ho = 0.399; He = 0.563) population was observed to have relatively lower genetic diversity compared to NRF (Ho = 0.659; He = 0.739) area based on the observed (Ho) and expected (He) heterozygosity value; and both areas shown a deficiency of heterozygosity indicated by positive FIS value (Tatau = 0.054; NRF = 0.165) that suggested the population undergoing inbreeding event. Furthermore, study on fungi diversity isolated from E. zwageri fruits identified fungi from nine taxa from Ascomycota phylum namely; Annulohypoxylon nites, A. viridistratum, Daldinia eschscholtzii, Hypoxylon investiens, Lasiodiplodia theobromae, Trichoderma asperellum, T. crassum, T. spirale, and T. virens. This data will be useful for future understanding in fungi involvement in rooted seed in E. zwageri species. It is hope that the results from this study will be used as baseline data in an effort to protect this vulnerable species.